New Hybrid Materials Synthesized with Different Dyes by Sol-Gel Method - Ramona Gheonea; Eleonora Cornelia Crasmareanu; Nicoleta Plesu; Sorin Sauca; Vasile Simulescu; Gheorghe Ilia (Advances in Materials Science and Engineering)
One well-known method for hybrids synthesis with incorporated organic dyes is sol-gel method, which is based on the concept of molecular manipulation to design ceramics, glasses, and composites. The low-temperature process allows for the incorporation of guest organic molecules within the inorganic matrix, as well as for the synthesis of hybrid networks in which the organic and inorganic phases are interpenetrating. The aim of the work presented in this paper was the preparation of the gels with three different dyes, at different molar ratios by using the hydrolytic sol-gel process. The interaction of the dye and the oxide was examined by UV-vis spectroscopy and FT-IR. The thermal stability of the hybrid organic-inorganic xerogel formed here was studied by thermal analysis. The micrographs obtained by scanning electron microscopy (SEM) revealed the high density of the films. Such characteristics indicate the possible application of these films in solar cells.